An Approach to Vacancy and Suspension of Regional and Local Authorities - Friz Burga, Johnny Zas (2007)
This paper examines the vacancy and suspension of regional and local authorities in Peru, with a case law approach. In this regard, the research conducted offers a synthesis of the most important points derived from the resolutions issued by the highest Peruvian electoral authority ―Jurado Nacional de Elecciones― regarding various cases of vacancy and suspension of such authorities. The objective is to provide an overview of the most transcendental elements regarding the vacancy and suspension, such as their causes, legal procedures, their regulation, their consequences and the challenges they present. Finally, it is highlighted that both the Organic Law of Regional Governments and the Organic Law of Municipalities could benefit from improvements in their regulation. These improvements would ultimately contribute to a more efficient management and operation of regional and municipal governments.